O29-3 Oil spill cleanup work and incident coronary heart disease in the gulf study. (1st September 2016) - Strelitz, Jean; Engel, Lawrence; Kwok, Richard; Miller, Aubrey; Blair, Aaron; Sandler, Dale
Abstract : Introduction: Workers involved in cleanup of the 2010 Deepwater Horizon oil spill faced exposures to crude oil, burning oil, and dispersants, in addition to physical and emotional stress. These exposures may contribute to the incidence of coronary heart disease (CHD). We assessed associations between several oil spill exposure proxies and incident nonfatal CHD. Methods: This analysis includes participants from the Gulf Long-term Follow-up (GuLF) STUDY who completed baseline interviews in 2011–2013. Participants include responders and non-responders who underwent mandatory worker safety training, government employees, and others. Total hydrocarbon (THC) exposure was estimated from a job exposure matrix characterised by cleanup tasks, and represents oil exposure. We estimated risk ratios (RR) and 95% confidence intervals for the associations of maximum THC exposure; work location; duration of cleanup work; and residential proximity to the spill with self-reported physician diagnosis of nonfatal CHD, adjusted for age, gender, education and smoking. Results: Of the 31, 609 participants included in the analyses, 77% worked on cleanup and 267 had new diagnoses of nonfatal CHD. Maximum THC exposure ≥3 parts per million (ppm) (vs < 0.03 ppm) was associated with a significant increased CHD risk [RR: 1.79 (1.09, 2.93)]. Working >180 days (vs 1–30 days) was nonsignificantly associated with increased risk [RR: 1.60 (0.93, 2.75)]. Living in a coastal county affected by the spill (vs living further away) was associated with significantly increased risk [RR: 1.47 (1.07–2.03)]. Analyses that restricted to the 188 myocardial infarction cases or that excluded diagnoses that occurred during the active cleanup period showed similar patterns of association. Conclusion: This is the first study to assess the relationship between oil spill cleanup work and CHD. Additional research is needed to determine if the observed associations are related to specific chemical exposures during cleanup or other stressors associated with the spill.